What$1 (Bs happening to grandpa? s - Shriver, Maria; Speidel, Sandra (Boston : Little, Brown/Warner Books, 2004)
Kate has always adored her grandpa$1 (Bs storytelling - but lately he$1 (Bs been repeating the same stories again and again. One day he even forgets Kate$1 (Bs name. Her mother$1 (Bs patient explanations open Kate$1 (Bs eyes to what so many of the elderly must confront: Alzheimer$1 (Bs disease and other forms of memory loss. With special insight derived from her own father$1 (Bs struggle with Alzheimer$1 (Bs, Maria Shriver offers a touching and optimistic story that encourages awareness, acceptance, and dialogue among family and friends.s
Keywords: Alzheimer$1 (Bs diseases -- Fiction; Grandfathers -- Fiction